2012
DOI: 10.1177/0959353512439188
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s like they don’t want you to get better’: Psy control of women in the carceral context

Abstract: This article examines how women incarcerated in provincial and federal prisons in Canada experience medicalization as the predominant form of correctional psy intervention. In order to privilege the oft ignored and typically silenced voices of incarcerated women, this article draws on life history interviews with 22 formerly incarcerated women who were living in halfway houses and working to transition from prison to the community. The analysis highlights the (over)use of prescription psychotropic medications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 20 publications
1
52
0
1
Order By: Relevance
“…There are considerable concerns that U.S. prisons are resorting to the use of psychotropic medication as a strategy for treating mentally ill incarcerated women (Kilty, 2012). However, research has also indicated that women in general society are much more likely to use drugs for mental health issues than men, with around a quarter of women in the United States taking some sort of medication (Medco, Inc., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…There are considerable concerns that U.S. prisons are resorting to the use of psychotropic medication as a strategy for treating mentally ill incarcerated women (Kilty, 2012). However, research has also indicated that women in general society are much more likely to use drugs for mental health issues than men, with around a quarter of women in the United States taking some sort of medication (Medco, Inc., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the categories I identified include research articles, again mostly qualitative, designed to improve mental health, health promotion, harm reduction, or legal advocacy practice with incarcerated women (Pedlar et al, 2008;Rehman, Gahagan, DiCenso, & Dias, 2004); methodology articles describing participatory action research methods (Martin et al, 2009); essays on program and policy reform (Alfred & Chlup, 2009;Kilty, 2012); and essays on the sociopolitical underpinnings of incarceration, which frequently call for political activism of various types (Allspach, 2010;Maidment, 2006;Reynolds, 2008). Kilty (2012) reviewed life history interviews with 22 formerly incarcerated Canadian women to argue that "psy" treatment (psychiatry and psychology) in prison is used for social control including discipline and punishment. She argues that, through processes of medicalization and pathologization, behavior interpreted as deviant is characterized as illness and treated with psychotropic medications; in essence, prison health care is reframed as a mechanism of behavioral control.…”
Section: Scholarly Feminist Literature On Incarcerated Womenmentioning
confidence: 99%
“…Authors such as Sherwood and Kendall (2013) write from a progressive, politicized viewpoint and call for the deconstruction of colonized nursing knowledge and relationships, but they would appear to be somewhat unique in this perspective. In contrast, the feminist literature routinely contains critiques and explorations of the politics of race, class, and gender as it relates to women's criminalization and calls for changes at the systemic, upstream level (Alfred & Chlup, 2009;Allspach, 2010;Haney, 2004;Kilty, 2012;Maidment, 2006;Reynolds, 2008).…”
Section: Comparison Of Articles From Each Body Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…While in the outside world, Chloe was able to make health choices that enabled her to manage her condition, inside the jail, she was forced to experience her illness as a salient aspect of her punishment. Her case also highlights the 'fallacy of self-governance' noted by Kilty (2012), whereby prisoners lose control over their bodies at the same time as they are expected to become responsibilized agents.…”
Section: "They Have a Hard Time When People Are Actually Aware Of Likmentioning
confidence: 96%